Pengembangan Media Pembelajaran KOMPA (Komik IPA) Materi Organ Pencernaan Manusia Menggunakan Model STAD Untuk Meningkatkan Hasil Belajar Siswa Kelas 5 SD - Agnesya Laely Hannyva; Mawardi Mawardi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research departs from the problem of using innovative learning media which is still inadequate. As a result, students feel bored and their learning outcomes are less than optimal. Based on these problems, this study aims to develop KOMPA learning media to improve student learning outcomes. The type of research used is research and development or called Research and Development (R&D). The subjects of this study were teachers and students of grade 5 SD Negeri Sumberejo 01. Data collection techniques in this study used tests, observation sheets, interview guides, documentation, assessment rubrics and questionnaires. The KOMPA product draft that has been developed is then validated by media experts, material experts, and learning design experts. The results of the validation of learning media experts get a score of 85%, material experts get 87.40%, and learning design experts get 96%. Limited test results for the assessment of student response questionnaires obtained 98%, teacher response questionnaire assessments obtained 90%. All the scores above, both the expert validation test results and student learning outcomes are in the very high category, this shows that the development of KOMPA learning media is feasible, effective and very practical to use in learning activities.